Successful intelligence and its relationship to lateral thinking among fifth-graders in mathematics (Czech Journal of Multidisciplinary Innovations, 2024)
The research aims to measure successful intelligence in its three areas of intelligence (analytical, practical and creative) and recognize lateral thinking with its skills (generating new realizations, generating new methods and methods, generating new ideas, generating new alternatives, generating new creations) and knowing the direction and strength of the correlation between successful intelligence and lateral thinking in fifth-graders in mathematics.